2015
DOI: 10.1590/1678-4162-7999
|View full text |Cite
|
Sign up to set email alerts
|

Eficácia do dipropionato de imidocarb, da enrofloxacina e do cloridrato de oxitetraciclina no tratamento de bovinos naturalmente infectados por Anaplasma marginale

Abstract:  RESUMOO agente de maior importância, em relação à anaplasmose bovina, é o Anaplasma marginale. Os principais sinais clínicos dessa enfermidade são anemia hemolítica, icterícia, dispneia, taquicardia, febre, fadiga, lacrimejamento, sialorreia, micção frequente, anorexia, perda de peso, aborto e morte. A terapia antimicrobiana é o principal protocolo terapêutico. O objetivo do presente trabalho foi avaliar a eficácia do dipropionato de imidocarb, da enrofloxacina e do cloridrato de oxitetraciclina no tratament… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The properties analyzed in the present study used drugs based on oxytetracycline and imidocarb dipropionate, and both drugs are effective in the treatment of bovine anaplasmosis. Following clinical recovery from the disease, animals remain carriers of the agent; thus, different protocols made with both drugs were not effective for the chemical sterilization of Anaplasma (Coetzee et al, 2005(Coetzee et al, , 2006Alberton et al, 2015). The recommended treatment protocols used were based only on imidocarb dipropionate for the treatment of CTF in the Northwest region of Minas Gerais state, and are inappropriate due to inefficiency in the treatment of bovine anaplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…The properties analyzed in the present study used drugs based on oxytetracycline and imidocarb dipropionate, and both drugs are effective in the treatment of bovine anaplasmosis. Following clinical recovery from the disease, animals remain carriers of the agent; thus, different protocols made with both drugs were not effective for the chemical sterilization of Anaplasma (Coetzee et al, 2005(Coetzee et al, , 2006Alberton et al, 2015). The recommended treatment protocols used were based only on imidocarb dipropionate for the treatment of CTF in the Northwest region of Minas Gerais state, and are inappropriate due to inefficiency in the treatment of bovine anaplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tais alterações quando acometem o encéfalo podem gerar diversos sintomas, dependendo da gravidade e da localização da lesão (DE CASTRO et al, 2004) ZAIDEN et al, 2023). Ou uma possível resistência ao primeiro fármaco utilizado, uma vez que, o dipropionato de imidocarb é uma base amplamente utilizada para o tratamento de diversas patologias, como anaplasmose, babesiose, erliquiose, toxoplasmose, em várias espécies (OGBU et al, 2018;ALBERTON et al, 2015;GREENE, 2015;SILVA et al, 2008).…”
Section: Relatounclassified
“…6,7 Other identified research provides evidence of ENR effectiveness for treatment of ANA. 2,3,5,10,12,15,17,18 In Brazil, an ENR 100 mg/mL product has a label indication for the treatment of ANA at a single, subcutaneous (SC) dosage of 3.4 mg/lb (7.5 mg/kg) of body weight (BW). a It has also been reported that an ENR dose of 5.7 mL/100 lb (5.7 mg/lb; 12.5 mg/kg) SC twice 48 h apart is effective for treatment of ANA.…”
Section: Introductionmentioning
confidence: 99%